PATHWAY TO CARE: HEALTH BELIEF MODEL AND BARRIERS IN MENTAL HEALTH SETTINGS - Mansoor, Sawera; Mansoor, Taskeen (Journal of Pakistan Psychiatric Society, 2022)
Objective: This study was planned to assess the pathway to mental health care including the health belief model and barriers faced by patients at a private tertiary care psychiatric facility in Rawalpindi, Pakistan Study Design: Cross sectional research Place and duration of study: This study was conducted from June to Dec 2016 at Fauji Foundation Hospital, Rawalpindi. Subjects and Methods: Through consecutive sampling, 246 patients presenting to the study venue were made part of the sample. A semi structured questionnaire was used to identify the symptom origin according to their health belief model as well as the barriers to care. Study variables were summarized using Descriptive statistics, and Chi square test was applied for association between common barriers to care and relevant socio-demographic variables using SPSS 20.0. Results: Out of 246 patients (61.4% females and 38.6% males), the majority of patients (39%) believed in a physical origin of their mental health symptoms followed by supernatural (32.9%) and psychological causes (28%). The most commonly reported type of barrier to care was Structural (68%) including Financial constraints and Lack of easy access to specialist resources whereas Attitudinal barriers such as Low perceived need and Perceived side effects of psychiatric medications were found in 22% of the cases. Stigma associated with psychiatric illnesses was reported by 10% cases. The educational status, locality of residence and monthly family income were significantly associated with structural and attitudinal barriers to mental health care. Conclusion: Patients with low literacy rates, rural based living and socioeconomic disadvantage are more likely to report structural and attitudinal barriers to accessing mental health services.